Learning at home during COVID-19 school closures – How do German students with and without special educational needs manage?. Issue 1 (1st January 2021) - Nusser, Lena
ABSTRACT: School closures due to the worldwide COVID-19 pandemic put challenges on teachers, students and their parents. In particular, students with special educational needs or students with low achievement levels who need more support in learning may have more difficulties coping compared to their peers. Using longitudinal data of the German National Educational Panel Study, the circumstances of students in secondary school during the time of school closures are characterised, in particular focusing on students who have been diagnosed with special educational needs or showing low achievement levels at the end of primary school. Overall, parents of students with special educational needs or low achievement levels do not report more challenges with respect to the situation of learning at home. However, differentiated results are found with regard to satisfaction with the support provided by the school, the amount of weekly learning time, and parental support. The situation of students with less favourable conditions in terms of learning at home by themselves needs special attention when face-to-face-instructions cannot be carried out as usual to achieve successful learning.